GO-TiO2 Nano Composites for Silicon PV Cell Application - Sai, P.H.V.S.T. (Elsevier Ltd, 2015)
Conventional multi crystalline silicon wafers used in photovoltaic applications offer lesser electrical conversion efficiencies due to various loss mechanisms. The key issues in conversion of photon energy to electrical energy by PV cell such as photon absorption, charge separation and carrier collection can be influenced by coating the active surface of the cell with nano composites as anti-reflection coating. Graphine oxide and TiO2 nano composites are having superior properties that can be used in many other applications apart from photo voltaic application. TiO2 is prepared using a two step sol-gel method using titanium isopropoxide as precursor. Graphine oxide is prepared using modified Hummer's method and is directly introduced into the structure of TiO2 to form the photo catalytic composite. Graphine oxide (GO) and titanium dioxide nano composites prepared using this simple and scalable method offers good photo-electrochemical properties. The extensive surface area of Graphine oxide and TiO2 and their excellent optical, chemical and mechanical properties are useful in tuning the band gap energy of the AR coating with reduced recombination rate and enhanced photocurrent. Characteristic studies on these GO-TiO2 composites resulted in enhanced conversion efficiencies of multi crystalline silicon solar cells compared to bare and TiO2 coated mc-Si cells. Â© 2015 Elsevier Ltd.